Leverage dynamics over the business cycle - Halling, Michael; Yu, Jin; Zechner, Josef (Journal of Financial Economics, 2016)
Surprisingly little is known about the business cycle dynamics of leverage. The existing evidence documents that target leverage evolves pro-cyclically either for all firms or financially constrained ones. In contrast, we show that, on average, target leverage ratios evolve counter-cyclically once cyclicality is measured comprehensively, accounting for variation in explanatory variables and model parameters. These counter-cyclical dynamics are robust to different subsamples of firms, data samples, empirical models of leverage, and definitions of leverage. There is a fraction of 10–25% of firms with pro-cyclical dynamics whose characteristics are consistent with counter-cyclical dynamics for loss-given-default and probability of default.